ANALYSIS AND SIMULATION ON DYNAMICAL MODELS OF THE MAGNETOR-HEOLOGICALDAMPER BASED ON MATLAB/SIMULINK - LI Cheng; ZHANG QianBin (Jixie qiangdu)
Magnetorheological damper is a kind of intelligent actuator for semi-active control. The dynamical models of Magneto-rheological damper was analyzed in this paper. The model of the extended Bingham and the modified Bouc-wen which were used widely was established by using Simulink. Then the simulation was carried out and the advantages and disadvantages of the two models were comparative analyzed. Finally,a new dynamical model with few parameters based on the tangent function was proposed. The physical meaning of the parameters were illustrated by simulation. The simulation results showed that the curve of the new model was smooth and accurate. It can be used for the simulation and study on the Magnetorheological Damper.